Pembelajaran Berbasis Proyek (PjBL) untuk Mengembangkan Kemampuan Berpikir Kritis Mahasiswa PGMI IAIN Ponorogo - Effendi, Mukhlison (IAIN Ponorogo, 2017)
This study is aimed at (1) seeking the light on the application of PjBL to improve critical thinking skills; (2) investigating the factors that influence PJBLs success in improving critical thinking skills; and (3) knowing the studentsâ responses to the application of PjBL which can improve critical thinking skills. The design used in this research was a qualitative case study. The result of the research was in the form of description and analysis of PjBL usage in improving students critical thinking skills in Mathematics Study unit at PGMI Department-FATIK, IAIN Ponorogo. Data were gained by using observation techniques, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusions. Validation of triangulation of data sources and methods was conducted. The results showed that the implementation of PjBL in improving critical thinking skills consisted of 3 stages: a) Planning the instructions using RPS; b) Implementing the actions into two face-to-face meeting periods in the classroom and out-of-classroom consultation process through online mode via WhatsAppÂ and offline with face-to-face on out-of-school hours.ÙÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¥ÙÙ: 1) Ù Ø¹Ø±ÙØ© ØªØ·Ø¨ÙÙ PjBL Ø§ÙØ°Ù Ø¨Ù ÙÙ ÙÙ ØªØ±ÙÙØ© ÙØ¯Ø±Ø© Ø§ÙØ·ÙØ§Ø¨ Ø¹ÙÙ Ø§ÙØªÙÙÙØ± Ø§ÙÙÙØ¯ÙØ 2) Ù Ø¹Ø±ÙØ© Ø§ÙØ¹ÙØ§Ù Ù Ø§ÙÙ Ø¤Ø«ÙØ±Ø© ÙÙØ¬Ø§Ø PjBL ÙÙ ØªØ±ÙÙØ© Ø§ÙÙØ¯Ø±Ø© Ø¹ÙÙ Ø§ÙØªÙÙÙØ± Ø§ÙÙÙØ¯ÙØ 3) Ù Ø¹Ø±ÙØ© Ø§Ø³ØªØ¬Ø§Ø¨Ø© Ø§ÙØ·ÙØ§Ø¨ Ø¹ÙÙ ØªØ·Ø¨ÙÙ PjBL Ø§ÙØ°Ù ÙØ³ØªØ·ÙØ¹ Ø£Ù ÙØ±ÙÙÙ Ø§ÙÙØ¯Ø±Ø© Ø¹ÙÙ Ø§ÙØªÙÙÙØ± Ø§ÙÙÙØ¯Ù. Ø§ØªØ¨Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙÙÙÙ Ø¨ÙÙØ¹ Ø¯Ø±Ø§Ø³Ø© ØØ§ÙØ©. ÙÙØªÙØ¬Ø© Ø§ÙØ¨ØØ« ÙÙ ØµÙØ±Ø© Ø§ÙØ¹Ø±Ø¶ ÙØªØÙÙÙ Ø§Ø³Ø®Ø¯Ø§Ù PjBL ÙÙ ØªØ±ÙÙØ© ÙØ¯Ø±Ø© Ø§ÙØ·ÙØ§Ø¨ Ø¹ÙÙ Ø§ÙØªÙÙÙØ± Ø§ÙÙÙØ¯Ù ÙÙ Ù Ø§Ø¯Ø© ØªØ¹ÙÙÙ Ø§ÙØ±ÙØ§Ø¶ÙÙØ§Øª ÙÙ ÙØ³Ù Ø§ÙØªØ±Ø¨ÙØ© ÙØ¥Ø¹Ø¯Ø§Ø¯ Ù Ø¯Ø±Ø³Ù Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ©Ø ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØ¹ÙÙÙ Ø§ÙØªØ¹ÙÙÙ ÙØ© Ø¨Ø§ÙØ¬Ø§Ù Ø¹Ø© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© ÙÙÙÙØ±ÙØ¬Ù. ÙØ¨ÙØ§ÙØ§Øª ÙØ°Ø§ Ø§ÙØ¨ØØ« ØªÙØ¬Ù Ø¹ Ø¨Ø·Ø±Ù Ø§ÙÙ ÙØ§ØØ¸Ø© ÙØ§ÙÙ ÙØ§Ø¨ÙØ© Ø§ÙØ´Ø®ØµÙØ© ÙØ§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙ ÙØªÙØ¨Ø©. Ø£Ù Ø§ ØªØÙÙÙÙØ§ ÙØ¨Ø·Ø±ÙÙØ© ØªØ®ÙÙØ¶ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø«Ù Ø¹Ø±Ø¶ÙØ§ ÙÙÙÙÙ Ø§ÙØ§Ø³ØªÙØªØ§Ø¬ Ù Ù Ø§ÙØ¨ÙØ§ÙØ§Øª. Ø£Ù Ø§ Ø§ÙØªØÙÙ Ù Ù ØµØØ© Ø§ÙØ¨ÙØ§ÙØ§Øª ÙØ¨Ø·Ø±ÙÙØ© Ø§ÙÙ ÙÙØ¬ Ø§ÙØªØ«ÙÙØ«Ù ÙÙ Ø§ÙÙ ØµØ§Ø¯Ø± ÙØ§ÙØ·Ø±Ù. Ø¯ÙÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù ØªØ·Ø¨ÙÙ PjBL ÙÙ ØªØ±ÙÙØ© Ø§ÙÙØ¯Ø±Ø© Ø¹ÙÙ Ø§ÙØªÙÙÙØ± Ø§ÙÙÙØ¯Ù ÙØªÙÙÙÙ Ù Ù Ø«ÙØ§Ø« Ù Ø±Ø§ØÙ : 1) Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙØªØ¹ÙÙÙ ÙÙ Ø´ÙÙ Ø®Ø·Ø· Ø§ÙØªØ¹ÙÙÙ Ø 2) ØªØ·Ø¨ÙÙ Ø§ÙØªØ¹ÙÙÙ Ù Ø±ÙØªÙÙ ÙÙ ØºØ±ÙØ© Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙØ¹Ù ÙÙØ© Ø§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø®Ø§Ø±Ø¬ ØºØ±ÙØ© Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹Ù Ø·Ø±ÙÙ Ø£ÙÙÙÙÙ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ù Ø±ÙÙ Ø§ÙÙØªØ³Ø§Ø¨ ÙØ¹Ù Ø·Ø±ÙÙ Ø¹Ø§Ø¯ÙÙ Ø¨Ø§ÙÙ ÙØ§Ø¨ÙØ© Ø®Ø§Ø±Ø¬ ØØµØ© Ø§ÙØ¯Ø±Ø§Ø³Ø©.